Pigment dispersion and aqueous coating composition and method for producing them
A copolymer and hydrocarbon group-containing acidic compound combination in the pigment dispersion addresses the challenge of stable pigment dispersion in water-based paints, achieving low viscosity and high color development in aqueous coating compositions.
Patent Information
- Application Number
- JP2023107340
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
AI Technical Summary
Existing water-based paint compositions face challenges in achieving stable and efficient pigment dispersion due to poor wetting with aqueous solvents and high viscosity, which affects the dispersibility and color development of the coating film.
A pigment dispersion comprising a copolymer with segments derived from nitrogen-containing polymerizable unsaturated monomers and polyoxyalkylene chains, combined with a hydrocarbon group-containing acidic compound, allows for stable dispersion of various pigments without increasing viscosity, using a specific ratio of acid groups to nitrogen-containing groups and incorporating a third segment from a hydroxyl group-containing monomer.
The solution results in a pigment dispersion with low viscosity and excellent dispersibility, enabling high color development and stability in aqueous coating compositions, suitable for a wide range of pigments.
Smart Images

Figure 2025006506000001 
Figure 2025006506000002 
Figure 2025006506000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a pigment dispersion and an aqueous coating composition, as well as methods for producing the same. [Background technology]
[0002] In recent years, there has been a demand for reducing emissions of volatile organic compounds (VOCs) from factories and other facilities in order to protect the environment. Water-based paint compositions have been proposed as one method for reducing VOC emissions. However, pigments are generally poorly wetted by aqueous solvents and have poor dispersibility.
[0003] In this regard, Patent Document 1 discloses an aqueous coating composition that contains a copolymer of multiple monomers including a polymerizable unsaturated monomer having a cationic functional group represented by a specific formula, a pigment, and an acid group- and hydroxyl group-containing acrylic resin. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2014-5399 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, with the copolymer of Patent Document 1, it is difficult to disperse a pigment sufficiently and stably. [Means for solving the problem]
[0006] In order to solve the above problems, the present invention provides the following aspects. [1] A composition comprising a copolymer (A), a hydrocarbon group-containing acidic compound (B), a pigment (C), and an aqueous solvent (D), The copolymer (A) is The copolymer has a first segment (a1) derived from a nitrogen-containing polymerizable unsaturated monomer having at least one of a tertiary amino group and a nitrogen-containing heterocyclic group, and a second segment (a2) derived from a polymerizable unsaturated monomer having a polyoxyalkylene chain, The hydrocarbon group-containing acidic compound (B) is A pigment dispersion having (b1) a saturated or unsaturated hydrocarbon group having 5 to 23 carbon atoms, and (b2) at least one acid group selected from the group consisting of a carboxy group, a phosphoric acid group, a sulfonic acid group, and a phenol group. [2] The pigment dispersion liquid according to the above-mentioned [1], wherein the ratio of the equivalent of the acid group contained in the hydrocarbon group-containing acidic compound (B) to the total equivalent of the tertiary amino group and the nitrogen-containing heterocyclic group contained in the copolymer (A) (acid group / tertiary amino group and nitrogen-containing heterocyclic group) is 0.5 or more and 2 or less. [3] The copolymer (A) further has a third segment (a3) derived from a polymerizable unsaturated monomer other than the nitrogen-containing polymerizable unsaturated monomer and the polymerizable unsaturated monomer having a polyoxyalkylene chain, In the copolymer (A), The mass proportion of the first segment (a1) is 5 mass% or more and 30 mass% or less, The mass proportion of the second segment (a2) is 20 mass% or more and 80 mass% or less, The pigment dispersion liquid according to the above [1] or [2], wherein the mass proportion of the third segment (a3) is 10 mass % or more and 60 mass % or less. [4] the third segment (a3) contains a segment (a31) derived from a hydroxyl group-containing polymerizable saturated monomer, The pigment dispersion liquid according to the above-mentioned [3], wherein the mass proportion of the segment (a31) in the copolymer (A) is 10 mass % or more and 30 mass % or less. [5] The pigment dispersion according to [1] or [2] above, and a film-forming resin. [6] A step of adding and mixing a hydrocarbon group-containing acidic compound (B) to a first mixture containing an aqueous solvent (D) and a copolymer (A) to obtain a second mixture; and adding and mixing a pigment (C) to the second mixture, The copolymer (A) is The copolymer has a first segment (a1) derived from a nitrogen-containing polymerizable unsaturated monomer having at least one of a tertiary amino group and a nitrogen-containing heterocyclic group, and a second segment (a2) derived from a polymerizable unsaturated monomer having a polyoxyalkylene chain, The hydrocarbon group-containing acidic compound (B) is A method for producing a pigment dispersion having a saturated or unsaturated hydrocarbon group (b1) having 5 to 23 carbon atoms and at least one acid group (b2) selected from the group consisting of a carboxy group, a phosphoric acid group, a sulfonic acid group, and a phenol group. [7] A method for producing an aqueous coating composition, comprising the step of mixing the pigment dispersion produced by the method described in [6] above with a coating film-forming resin. Effect of the Invention
[0007] According to the present disclosure, a pigment dispersion liquid having low viscosity and excellent pigment dispersibility is provided, regardless of the type of pigment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] A pigment dispersant is an additive used to uniformly disperse a pigment in a solvent, and has a hydrophilic portion and a hydrophobic portion, similar to a surfactant. There are various types of hydrophilic portions. The hydrophilic portion can be ionized to generate anions or cations, and may not have ionic dissociation properties.
[0009] Pigments usually have acidic sites, basic sites or inactive sites on their surface, and exhibit acidic, basic, hydrophobic or hydrophilic properties. These properties are not clearly distinguishable for each pigment, and may have composite properties. It is difficult to select a pigment dispersant suitable for a pigment having such various properties. Therefore, a pigment dispersant that can be used for any pigment is desired. However, if one pigment dispersant (compound) has multiple functional groups that can correspond to each of the above sites, problems such as an increase in the viscosity of the pigment dispersion due to association or the like may occur. Similarly, when multiple types of pigment dispersants are used in combination, the viscosity of the pigment dispersion may increase, or problems may occur in terms of the affinity between the pigment dispersant and the solvent. The increase in the viscosity of the pigment dispersion makes it difficult to prepare a coating composition, and may also be a factor in reducing the dispersibility of the pigment in the pigment dispersion.
[0010] The smaller the particle size of the pigment in the coating film (i.e., the higher the dispersibility of the pigment in the coating composition and, ultimately, in the pigment dispersion), the better the color development of the coating film. In general, the smaller the particle size of the pigment (the higher the dispersibility of the pigment), the higher the viscosity of the pigment dispersion. In other words, if the dispersibility of the pigment in the pigment dispersion is increased in order to improve the color development of the coating film, the viscosity of the pigment dispersion increases. This makes it difficult to mix the pigment dispersion with the coating film-forming resin, which can result in a decrease in pigment dispersibility in the coating composition. Usually, it can be said that there is a trade-off between improved color development of the coating film (improved pigment dispersibility) and lowering the viscosity of the pigment dispersion.
[0011] In the present disclosure, a combination of compounds (pigment dispersants) that can disperse a pigment well in a polar solvent (aqueous solvent) without causing an increase in viscosity, regardless of the nature of the pigment, has been discovered. A coating composition obtained by using the pigment dispersion according to the present disclosure has high color development properties.
[0012] The pigment dispersion according to the present disclosure includes a copolymer (A), a hydrocarbon group-containing acidic compound (B) (hereinafter sometimes referred to as "organic acid (B)"), a pigment (C), and an aqueous solvent (D). The copolymer (A) has a first segment (a1) derived from a nitrogen-containing polymerizable unsaturated monomer having at least one of a tertiary amino group and a nitrogen-containing heterocyclic group, and a second segment (a2) derived from a polymerizable unsaturated monomer having a polyoxyalkylene chain. The organic acid (B) has a saturated or unsaturated hydrocarbon group (b1) having 4 to 18 carbon atoms, and at least one acid group (b2) selected from the group consisting of a carboxylic acid group, a phosphoric acid group, a sulfonic acid group, and a phenol group.
[0013] In the copolymer (A), the tertiary amino group and / or nitrogen-containing heterocyclic group (hereinafter sometimes referred to as "nitrogen-containing group") of the first segment (a1) and the polyoxyalkylene chain of the second segment (a2) are both arranged as side chains. The main chain of the copolymer (A) is composed of carbon-carbon bonds. In the organic acid (B), the acid group (b2) is usually located at the end of the hydrocarbon group (b1).
[0014] The nitrogen-containing group in the first segment (a1) of the copolymer (A) generates a cation in an aqueous solvent. The acid group of the organic acid (B) generates an anion in an aqueous solvent. Therefore, the copolymer (A) and the organic acid (B) can exist as counter ions of each other in the aqueous solvent. The saturated or unsaturated hydrocarbon group (hereinafter sometimes simply referred to as "hydrocarbon group") of the organic acid (B) basically does not have ionic dissociation properties.
[0015] The combination of the copolymer (A) and the organic acid (B) improves the dispersibility of various pigments without increasing the viscosity, and the reason for this is thought to be as follows, without being bound by any particular theory. When the pigment (C) has acidic properties (hereinafter, for convenience, it may be referred to as an "acidic pigment"; typically, carbon black), the copolymer (A) can be adsorbed to the pigment (C) by the nitrogen-containing group. Specifically, the nitrogen-containing group is adsorbed to the pigment (C), and the polyoxyalkylene chain is arranged on the outside of the pigment (C). Furthermore, the polyoxyalkylene chain is arranged so as to extend toward the outside of the pigment (C) due to chemical and steric repulsion with the hydrophobic main chain of the copolymer (A). The polyoxyalkylene chain extending toward the outside can suppress aggregation of the pigments (C) that have adsorbed the copolymer (A).
[0016] Furthermore, the acid group of the organic acid (B) may exist as a counter ion in the vicinity of the nitrogen-containing group, so that the charge balance is maintained and aggregation of the pigments (C) is further suppressed.
[0017] In addition, the main chain of the copolymer (A) and the hydrocarbon group of the organic acid (B) are both hydrophobic and have a high affinity. Therefore, the pigment (C) can strongly adsorb the organic acid (B) in addition to the copolymer (A). On the other hand, the polyoxyalkylene chain has a high affinity with the aqueous solvent (D). In other words, the pigment (C) that has adsorbed the copolymer (A) and the organic acid (B) is dispersed in the aqueous solvent (D) in a state where the hydrophobic parts of the copolymer (A) and the organic acid (B) are surrounded by the hydrophilic polyoxyalkylene chain, so it is difficult to aggregate and is believed to be able to be dispersed while maintaining this state.
[0018] From another perspective, the copolymer (A) having a polyoxyalkylene chain disperses the organic acid (B) having a relatively long-chain hydrocarbon group uniformly in the aqueous solvent (D). The organic acid (B) having a hydrocarbon group (b1) can reduce the surface tension of the aqueous solvent (D). The reduction in the surface tension of the aqueous solvent (D) improves the wettability of the pigment (C) to the aqueous solvent. As described above, since the organic acid (B) is uniformly dispersed in the aqueous solvent (D) together with the pigment (C), the effect of reducing the surface tension is further enhanced, and the wettability of the pigment (C) to the aqueous solvent (D) can be further improved. As a result, the cohesive force between the pigments (C) is further weakened, and the pigment dispersibility in the aqueous solvent (D) is further improved. The dispersion stability of the pigment (C) can also be improved.
[0019] By using the organic acid (B) in combination, the copolymer (A) can be relatively freely selected as long as it has the first segment (a1) and the second segment (a2). In other words, when preparing the aqueous coating composition, the design freedom is expanded, and a copolymer (A) more suitable for the pigment (C) can be used.
[0020] When the pigment (C) has basic properties (hereinafter, for convenience, it may be referred to as "basic pigment"), the organic acid (B) is adsorbed to the pigment (C) by the acid group (b2). A nitrogen-containing group, which is a counter ion, may be present in the vicinity of the acid group. In other words, in this case, the copolymer (A) and the organic acid (B) can be present in the vicinity of each other. Therefore, the polyoxyalkylene chain of the copolymer (A) is arranged so as to extend toward the outside of the pigment (C) due to chemical and steric repulsion with the hydrocarbon group (b1) of the organic acid (B) and the hydrophobic main chain of the copolymer (A), suppressing the aggregation of the pigments. In addition, as in the case of acidic pigments, the organic acid (B) has the effect of reducing the surface tension of the aqueous solvent, etc., thereby improving the pigment dispersibility and further the dispersion stability of the pigment (C).
[0021] When the pigment (C) has hydrophobic properties (hereinafter, for convenience, it may be referred to as a "hydrophobic pigment"; typically, phthalocyanine blue), the organic acid (B) is adsorbed to the pigment (C) by hydrophobic interaction with the hydrocarbon group (b1). Therefore, the dispersibility and dispersion stability of the pigment (C) are improved by the same action as in the case of a basic pigment.
[0022] As described above, by using the copolymer (A) having a group that is easily adsorbed to an acidic pigment and the organic acid (B) having a group that is easily adsorbed to a basic or hydrophobic pigment in combination, various pigments (C) can be dispersed. Furthermore, since the copolymer (A) and the organic acid (B) exist as counter ions, the charge balance is maintained, the effect of reducing the surface tension is enhanced, and the pigment (C) can be stably present in a finely divided state in the pigment dispersion. In addition, since the nitrogen-containing group and the acid group are provided in separate compounds, the occurrence of an interaction between the two is suppressed, and an increase in the viscosity of the pigment dispersion is suppressed. Since the polyoxyalkylene chain is non-ionic dissociable, it is difficult for an interaction to occur between the nitrogen-containing group in the same compound.
[0023] The pigment dispersion according to the present disclosure has a low viscosity despite containing a finely divided pigment, and therefore, when preparing an aqueous coating composition, the pigment dispersion can be easily mixed with a coating film-forming resin, and the pigment dispersibility in the aqueous coating composition is improved.
[0024] [Pigment dispersion] The pigment dispersion according to the present disclosure includes a copolymer (A), an organic acid (B), a pigment (C), and an aqueous solvent (D). The copolymer (A) has a first segment (a1) derived from a nitrogen-containing polymerizable unsaturated monomer having a nitrogen-containing group, and a second segment (a2) derived from a polymerizable unsaturated monomer having a polyoxyalkylene chain. The organic acid (B) has a hydrocarbon group (b1) having 4 to 18 carbon atoms and an acid group (b2). The pigment dispersion includes the aqueous solvent (D) and is aqueous.
[0025] The copolymer (A) and organic acid (B) described above allow various pigments (C) to be well dispersed in the aqueous solvent (D) without causing an increase in viscosity. That is, the pigment dispersion according to the present disclosure has a low viscosity, and the pigment is well dispersed in the pigment dispersion (in other words, the average particle size of the pigment is small).
[0026] The copolymer (A) and the organic acid (B) can be blended so that the ratio of the equivalent of the acid group (b2) of the organic acid (B) to the total equivalent of the nitrogen-containing group of the copolymer (A) (acid group / nitrogen-containing group) is 0.5 or more and 2 or less. When the equivalent ratio (acid group / nitrogen-containing group) is 0.5 or more, the effect of improving the pigment dispersibility is more easily obtained. When the equivalent ratio (acid group / nitrogen-containing group) is 2 or less, the effect of dispersing the organic acid (B) by the copolymer (A) is more enhanced, and the effect of improving the dispersion stability is more easily obtained. The equivalent ratio (acid group / nitrogen-containing group) may be 0.6 or more, or 0.8 or more. The equivalent ratio (acid group / nitrogen-containing group) may be 1.8 or less, or 1.5 or less.
[0027] The pigment (C) is blended, for example, in an amount of 30 parts by mass or more and 3000 parts by mass or less per 100 parts by mass of the solid content of the copolymer (A). The blending amount of the pigment (C) may be 45 parts by mass or more, or 60 parts by mass or more. The blending amount of the pigment (C) may be 2800 parts by mass or less, or 2700 parts by mass or less.
[0028] The solid content concentration of the pigment dispersion is, for example, 5% by mass or more and 90% by mass or less. The solid content concentration of the pigment dispersion may be 8% by mass or more, or 10% by mass or more. The solid content concentration of the pigment dispersion may be 88% by mass or less, or 85% by mass or less.
[0029] The solids concentration of the pigment dispersion is measured in accordance with JIS K 5601-1-2 Heat Residue Measurement Method.
[0030] The pigment (C) is finely dispersed in the pigment dispersion. The average particle size of the pigment (C) in the pigment dispersion can be, for example, 90% or more and 1000% or less of the primary particle size of the pigment (C). When the average particle size of the pigment (C) in the pigment dispersion is within this range, it can be said that the pigment (C) is suppressed from aggregating and is finely divided. The average particle size of the pigment (C) in the pigment dispersion can be 900% or less, or 800% or less of the primary particle size of the pigment (C).
[0031] The average particle size refers to the volume average particle size D50, which is the 50% average particle size (D50) in the volume-based particle size distribution measured using a laser diffraction / scattering particle size distribution measuring device (e.g., trade name: UPA-150, manufactured by Microtrac).
[0032] Pigment dispersions have various viscosities depending on the type of pigment. It is desirable for the viscosity of the pigment dispersion to be low so that the coating composition can be easily prepared. The viscosity of the pigment dispersion at 25° C. and a rotation speed of 5 rpm may be, for example, 5000 cps or less, or 2000 cps or less. The lower limit of the viscosity of the pigment dispersion is appropriately set depending on the type and size of the pigment (C), and is not particularly limited.
[0033] The pigment dispersion according to the present disclosure has a sufficiently lower viscosity than other pigment dispersions in which the same pigment is dispersed to a similar particle size using a pigment dispersant other than the copolymer (A) and / or the organic acid (B). For example, the viscosity of the pigment dispersion according to the present disclosure may be about 1 / 2 or less, or about 1 / 3 or less, of the viscosity of the other pigment dispersions described above. Alternatively, the pigment dispersion according to the present disclosure may have a smaller particle size than yet another pigment dispersion in which the same pigment is dispersed to a degree that does not cause an increase in viscosity using a pigment dispersant other than the copolymer (A) and / or the organic acid (B). For example, the average particle size of the pigment contained in the pigment dispersion according to the present disclosure may be about 80% or less, about 75% or less, or about 70% or less of the average particle size of the pigment contained in the yet another pigment dispersion.
[0034] (A) Copolymer The copolymer (A) has a first segment (a1) derived from a nitrogen-containing polymerizable unsaturated monomer having a nitrogen-containing group (hereinafter may be referred to as a "nitrogen-containing monomer"), and a second segment (a2) derived from a polymerizable unsaturated monomer having a polyoxyalkylene chain (hereinafter may be referred to as a "hydrophilic monomer").
[0035] The first segment (a1) has at least one nitrogen-containing group. The nitrogen-containing group generates a cation in an aqueous solvent and can be adsorbed to an acidic pigment. In addition, the nitrogen-containing group does not have an active hydrogen that chemically reacts with a component (typically a curing agent) blended in the aqueous coating composition, so it is difficult to inhibit the curing reaction of the aqueous coating composition.
[0036] The second segment (a2) has at least one polyoxyalkylene chain, which inhibits pigment particles from approaching each other, thereby contributing to suppression of aggregation, and also enhances the hydrophilicity of the copolymer (A).
[0037] The copolymer (A) may further have a third segment (a3) derived from a polymerizable unsaturated monomer other than the nitrogen-containing monomer and the hydrophilic monomer.
[0038] The mass proportion of the first segment (a1) may be 5% by mass or more and 30% by mass or less, the mass proportion of the second segment (a2) may be 20% by mass or more and 80% by mass or less, and the mass proportion of the third segment (a3) may be 10% by mass or more and 60% by mass or less.
[0039] When the mass proportion of the first segment (a1) is 5% by mass or more, the pigment adsorption performance is improved. When the mass proportion of the first segment (a1) is 30% by mass or less, the hydrophilicity of the copolymer (A) is prevented from becoming excessively high, and the deterioration of the water resistance of the coating film is prevented. The mass proportion of the first segment (a1) may be 7% by mass or more, 10% by mass or more, or 12% by mass or more. The mass proportion of the first segment (a1) may be 27% by mass or less, 25% by mass or less, or 22% by mass or less.
[0040] When the mass proportion of the second segment (a2) is 20% by mass or more, the dispersibility of the pigment adsorbed with the copolymer (A) is improved. When the mass proportion of the second segment (a2) is 80% by mass or less, the hydrophilicity of the copolymer (A) is prevented from becoming excessively high, and the deterioration of the water resistance of the coating film is prevented. The mass proportion of the second segment (a2) may be 30% by mass or more, 35% by mass or more, or 40% by mass or more. The mass proportion of the second segment (a2) may be 75% by mass or less, 70% by mass or less, or 65% by mass or less.
[0041] The mass percentage of the third segment (a3) may be, for example, 10% by mass or more and 60% by mass or less. The mass percentage of the third segment (a3) may be 15% by mass or more, or 20% by mass or more. The mass percentage of the third segment (a3) may be 55% by mass or less, or 50% by mass or less.
[0042] The third segment (a3) may contain a segment derived from a hydroxyl-containing polymerizable unsaturated monomer (hereinafter referred to as hydroxyl-containing segment (a31)). The hydroxyl group can chemically react with the components blended in the aqueous coating composition. The copolymer (A) adsorbed to the pigment reacts chemically with the curing agent, thereby preventing the pigment from falling off (bleeding out) from the coating film. The mass ratio of the hydroxyl-containing segment (a31) may be 10% by mass or more and 30% by mass or less. When the mass ratio of the hydroxyl-containing segment (a31) is in this range, the effect of preventing bleed-out is easily exhibited, and the viscosity of the pigment dispersion is less likely to increase. The mass ratio of the hydroxyl-containing segment (a31) may be 12% by mass or more, or 15% by mass or more. The mass ratio of the hydroxyl-containing segment (a31) may be 25% by mass or less, or 20% by mass or less.
[0043] The content of the first segment (a1) in all structural units can be calculated by dividing the charged mass of the nitrogen-containing polymerizable unsaturated monomer used in synthesizing the copolymer (A) by the total charged mass of all raw material monomers. Similarly, the content of the other segments in all structural units can be calculated by dividing the charged mass of the monomer forming the segment used in synthesizing the copolymer (A) by the total charged mass of all raw material monomers.
[0044] The weight average molecular weight of the copolymer (A) may be 10,000 or more and 40,000 or less. The weight average molecular weight of the copolymer (A) may be 15,000 or more and 20,000 or more. The weight average molecular weight of the copolymer (A) may be 38,000 or less and 35,000 or less.
[0045] The weight average molecular weight can be calculated from a chromatogram measured by gel permeation chromatography, based on the molecular weight of standard polystyrene. The acid value and hydroxyl value are calculated from the monomer composition used in the preparation, in accordance with JIS regulations.
[0046] (Nitrogen-containing polymerizable unsaturated monomer) The nitrogen-containing polymerizable unsaturated monomer (nitrogen-containing monomer) has at least one of a tertiary amino group and a nitrogen-containing heterocyclic group, and a polymerizable unsaturated group in one molecule. The tertiary amino group and the nitrogen-containing heterocyclic group are basic. Therefore, the (a1) first segment derived from the nitrogen-containing monomer can be well adsorbed to a pigment having an acidic site (e.g., carbon black).
[0047] Examples of the tertiary amino group-containing monomer include N,N-dialkylaminoalkyl (meth)acrylates such as N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, N,N-di-t-butylaminoethyl (meth)acrylate, and N,N-dimethylaminobutyl (meth)acrylate; and N,N-dialkylaminoalkyl (meth)acrylamides such as N,N-dimethylaminoethyl (meth)acrylamide, N,N-diethylaminoethyl (meth)acrylamide, and N,N-dimethylaminopropyl (meth)acrylamide. These may be used alone or in combination of two or more.
[0048] Among them, it may be N,N-dialkylaminoalkyl(meth)acrylate, N,N-dimethylaminoethyl(meth)acrylate and N,N-diethylaminoethyl(meth)acrylate.
[0049] In this specification, "(meth)acrylic" is a concept including both acrylic and methacrylic.
[0050] Examples of the nitrogen-containing heterocyclic group include a pyridine ring group, a quinoline ring group, a thiazole ring group, an oxazole ring group, a benzothiazole ring group, an imidazole ring group, a pyrazole ring group, an imidazoline ring group, a pyrimidine ring group, a pyrazine ring group, a triazole ring group, and a tetrazole ring group.
[0051] Examples of polymerizable unsaturated monomers (vinyl monomers) having a pyridine ring include 2-vinylpyridine and 4-vinylpyridine. Examples of polymerizable unsaturated monomers having a thiazole ring include 2-vinylthiazole and 4-methyl-5-vinylthiazole. Examples of polymerizable unsaturated monomers having an oxazole ring include 2-phenyl-5-vinyloxazole. Examples of polymerizable unsaturated monomers having a benzothiazole ring include 2-vinylbenzothiazole, 2-[2-(1-naphthyl)vinyl]benzothiazole, and 2-[2-(dimethylamino)vinyl]benzothiazole. Examples of polymerizable unsaturated monomers having an imidazole ring include 1-vinylimidazole, 2-methyl-1-vinylimidazole, 2-vinylimidazole, 4-vinylimidazole, 2-phenyl-1-vinylimidazole, 1-vinylcarbazole, and 2-(1H-imidazol-1-yl)ethyl (meth)acrylate. Examples of the polymerizable unsaturated monomer having a pyrazole ring include 1-vinylpyrazole and 3-vinylpyrazole. Examples of the polymerizable unsaturated monomer having an imidazoline ring include 1-vinyl-2-imidazoline, 1-vinyl-2-methylimidazoline, 2-vinyl-2-imidazoline, and 2-(1H-imidazolin-1-yl)ethyl (meth)acrylate. Examples of the polymerizable unsaturated monomer having a pyrimidine ring include 5-vinylpyrimidine and 2,4-dichloro-6-vinylpyrimidine. Examples of the polymerizable unsaturated monomer having a pyrazine ring include 2-vinylpyrazine, 2,5-dimethyl-3-vinylpyrazine, and 2-methyl-5-vinylpyrazine. Examples of the vinyl monomer having a triazole ring include 2,4-diamino-6-vinyltriazine. Examples of polymerizable unsaturated monomers having a tetrazole ring include 1-vinyl-1H-tetrazole, 2-vinyl-2H-tetrazole, 5-vinyl-1H-tetrazole, and 1-methyl-5-vinyl-1H-tetrazole. These may be used alone or in combination of two or more.
[0052] Among these, at least one of a vinyl monomer having a pyridine ring group and a vinyl monomer having an imidazole ring group may be used.
[0053] Among them, the nitrogen-containing monomer may be an N,N-dialkylaminoalkyl(meth)acrylate. This further improves the dispersibility of the pigment. A preferred N,N-dialkylaminoalkyl(meth)acrylate is represented by the following general formula: [ka]
[0054] In the formula, A represents hydrogen or a methyl group, B 1 and B. 2 each independently represents a linear or branched hydrocarbon group having 1 to 4 carbon atoms, and n is an integer of 1 to 3. In the formula, A may be a methyl group, B 1 and B. 2 may be a hydrocarbon group having 1 or 2 carbon atoms, and n may be 1 or 2.
[0055] (Polymerizable unsaturated monomer having a polyoxyalkylene chain) The polymerizable unsaturated monomer having a polyoxyalkylene chain (hydrophilic monomer) has a polyoxyalkylene chain and a polymerizable unsaturated group in one molecule. The second segment (a2) derived from the hydrophilic monomer imparts hydrophilicity to the copolymer (A).
[0056] The polyoxyalkylene chain may be, for example, a polyoxyethylene chain, a polyoxypropylene chain, a chain containing a polyoxyethylene block and a polyoxypropylene block. The proportion of the polyoxyethylene chain in the total polyoxyalkylene chain may be 65% by mass or more, 70% by mass or more, 75% by mass or more, or 80% by mass or more. In one embodiment, the polyoxyalkylene chain is composed of polyoxyethylene.
[0057] The molecular weight of the polyoxyalkylene chain is, for example, 200 or more and 5,000 or less. From the viewpoint of dispersion stability, the molecular weight of the polyoxyalkylene chain may be 300 or more, 400 or more, 800 or more, or 1,000 or more. The molecular weight of the polyoxyalkylene chain may be 3,500 or less, or 2,500 or less. In particular, when the molecular weight of the polyoxyalkylene chain is 800 or more, long-term dispersion stability is easily obtained.
[0058] Examples of hydrophilic monomers include acrylates having a polyoxyethylene chain such as tetraethylene glycol (meth)acrylate, methoxytetraethylene glycol (meth)acrylate, ethoxytetraethylene glycol (meth)acrylate, n-butoxytetraethylene glycol (meth)acrylate, polyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and ethoxypolyethylene glycol (meth)acrylate; and acrylates having a polyoxypropylene chain such as tetrapropylene glycol (meth)acrylate, methoxytetrapropylene glycol (meth)acrylate, ethoxytetrapropylene glycol (meth)acrylate, n-butoxytetrapropylene glycol (meth)acrylate, and polypropylene glycol (meth)acrylate. These may be used alone or in combination of two or more.
[0059] (Other polymerizable unsaturated monomers) The other polymerizable unsaturated monomers (hereinafter sometimes referred to as "other raw material monomers") have a polymerizable unsaturated group in one molecule, but do not have a polyoxyalkylene chain or a nitrogen-containing group. The third segment (a3) derived from the other raw material monomers can impart various functions to the copolymer (A).
[0060] The other raw material monomers desirably do not have acid groups such as carboxy groups, phosphoric acid groups, sulfonic acid groups, and phenol groups, because interactions between the acid groups and the nitrogen-containing groups can cause intermolecular forces in the copolymer (A), resulting in an excessively high viscosity of the pigment dispersion.
[0061] The other raw material monomer may have a hydroxyl group and a polymerizable unsaturated group in one molecule. The hydroxyl group can chemically react with the curing agent blended in the aqueous coating composition, so that the water resistance of the resulting coating film can be improved. Furthermore, the copolymer (A) adsorbed on the pigment (C) can chemically react with the curing agent, which can easily prevent the pigment from falling off (bleeding out) from the coating film.
[0062] Examples of hydroxyl group-containing polymerizable unsaturated monomers (hereinafter sometimes referred to as "hydroxyl group-containing monomers") include monoesters of (meth)acrylic acid and dihydric alcohols having 2 to 8 carbon atoms, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; ε-caprolactone-modified monoesters of (meth)acrylic acid and dihydric alcohols having 2 to 8 carbon atoms; and allyl alcohol. These may be used alone or in combination of two or more.
[0063] Examples of raw material monomers other than the hydroxyl group-containing monomer include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, and tert-butyl (meth)acrylate; vinyl aromatic compounds such as styrene, α-methylstyrene, and vinyl toluene; (meth)acrylonitrile, (meth)acrylamide, and vinyl acetate. These may be used alone or in combination of two or more.
[0064] (B)Organic acid The organic acid (B) has a hydrocarbon group (b1) and an acid group (b2). The acid group (b2) is typically located at the terminal of the hydrocarbon group (b1).
[0065] The hydrocarbon group (b1) may be saturated or unsaturated. The hydrocarbon group (b1) may be linear, alicyclic, or may have an aromatic ring. In particular, from the viewpoint of color development, the hydrocarbon group (b1) may be linear. The linear hydrocarbon group (b1) may be linear or branched.
[0066] The number of carbon atoms in the hydrocarbon group (b1) is 5 to 23. When the organic acid (B) has a relatively long hydrocarbon group (b1), the hydrophobic pigment is easily adsorbed to the organic acid (B), the polyoxyalkylene chain is easily extended outward, and the surface tension of the aqueous solvent is easily reduced. In addition, when preparing an aqueous coating composition, the organic acid (B) is prevented from dissociating from the pigment to which the organic acid (B) is adsorbed, and the dispersibility of the pigment in the aqueous coating composition is maintained. On the other hand, if the number of carbon atoms in the hydrocarbon group (b1) is excessively large, it is difficult to uniformly disperse the pigment in the aqueous solvent. The number of carbon atoms in the hydrocarbon group (b1) may be 6 or more, 7 or more, or 12 or more. The number of carbon atoms in the hydrocarbon group (b1) may be 21 or less, or 19 or less.
[0067] The acid group (b2) is at least one selected from the group consisting of a carboxy group, a phosphoric acid group, a sulfonic acid group, and a phenol group. The organic acid (B) may have a plurality of the same or different acid groups (b2), or may have one acid group (b2).
[0068] Examples of organic acids (B) having a carboxy group include monovalent, divalent and trivalent organic carboxylic acids. Examples of monovalent organic carboxylic acids include caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, isostearic acid, undecylenic acid, petroselinic acid, oleic acid, ricinoleic acid, linoleic acid, linolenic acid and cyclohexane carboxylic acid. Examples of divalent organic carboxylic acids include fumaric acid, maleic acid, adipic acid, pimelic acid, suberic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid and 1,4-cyclohexane dicarboxylic acid. Examples of trivalent organic carboxylic acids include aconitic acid. Other examples of organic acids (B) having a carboxy group include amino acids and their derivatives (e.g. trimethylated amino acids such as trimethylglycine).
[0069] Examples of the organic acid (B) having a phosphoric acid group include alkylphosphonic acids (such as octylphosphonic acid), alkenylphosphonic acids (such as oleyl phosphate), and phenylphosphinic acids.
[0070] Examples of the organic acid (B) having a sulfonic acid group include paraphenylbenzenesulfonic acid, β-naphthalenesulfonic acid, naphthol-1-sulfonic acid, p-toluenesulfonic acid, p-benzenechlorosulfonic acid, and 5-chloro-α,α-bis(3,5-dichloro-2-hydroxyphenyl)toluenesulfonic acid.
[0071] Examples of the organic acid (B) having a phenol group include nonylphenol, t-butylphenol, and t-butylcatechol.
[0072] (C) Pigment Examples of the pigment include color pigments, extender pigments, anti-rust pigments, and luster pigments. The color pigment may be inorganic or organic. The color pigment may be chromatic or achromatic. Examples of organic color pigments include azo chelate pigments, insoluble azo pigments, condensed azo pigments, diketopyrrolopyrrole pigments, phthalocyanine pigments, indigo pigments, perinone pigments, perylene pigments, dioxane pigments, quinacridone pigments, isoindolinone pigments, and metal complex pigments. Examples of inorganic color pigments include yellow lead, yellow iron oxide, red iron oxide, carbon black, and titanium dioxide. These may be used alone or in combination of two or more.
[0073] Examples of the extender pigment include calcium carbonate, barium sulfate, clay, and talc. These may be used alone or in combination of two or more.
[0074] Examples of the luster pigment include mica pigments such as interference mica, white mica, and colored mica; graphite pigments; glass flake pigments; and metal pigments such as aluminum, copper, zinc, iron, nickel, tin, aluminum oxide, chromium oxide, and alloys containing these. These may be used alone or in combination of two or more. The luster pigment may be colored.
[0075] (D) Aqueous Solvent The aqueous solvent (D) accounts for 50% by mass or more of the total solvent in the pigment dispersion liquid. Examples of the aqueous solvent (D) include water and a mixture of water and a hydrophilic solvent.
[0076] Examples of hydrophilic solvents include glycol solvents such as ethylene glycol, propylene glycol, butanediol, pentanediol, diethylene glycol, dipropylene glycol, and triethylene glycol; glycol ether solvents such as ethylene glycol monobutyl ether (butyl cellosolve), diethylene glycol monobutyl ether, diethylene glycol dibutyl ether, triethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, and propylene glycol monomethyl ether acetate; alcohol solvents such as methanol, ethanol, and isopropyl alcohol; ketone solvents such as acetone; and N-methyl-2-pyrrolidone. These may be used alone or in combination of two or more.
[0077] (others) The pigment dispersion may contain other components such as a defoamer, an ultraviolet absorber, a light stabilizer, an antioxidant, a surface conditioner, a film-forming assistant, and a rust inhibitor.
[0078] [Method of manufacturing pigment dispersion] The pigment dispersion according to the present disclosure is produced by a method including a step of adding and mixing an organic acid (B) to a first mixture containing an aqueous solvent (D) and a copolymer (A) to obtain a second mixture, and a step of adding and mixing a pigment (C) to the second mixture.
[0079] By first mixing the copolymer (A) with the aqueous solvent (D) and then mixing the organic acid (B), the organic acid (B) becomes more easily dissolved and / or dispersed in the aqueous solvent (D), and the dispersibility of the pigment (C) is further improved.
[0080] Each mixing is carried out, for example, by using a disperser (agitator). Examples of dispersers include low-speed agitators such as a propeller mixer, a paddle mixer, and an anchor mixer, and high-speed agitators such as a homo mixer, a disperser mixer, and an ultra mixer.
[0081] The obtained pigment dispersion may be further mixed by a dispersing machine using a dispersing media (beads). This promotes the fine particle formation of the pigment (C). Specific examples of dispersing machines include Ultra Apex Mill, trade name: Dual Apex Mill (Kotobuki Industries Co., Ltd.), Paint Conditioner, Picograin Mill, trade name: Eco Mill (Asada Iron Works Co., Ltd.), Star Mill ZRS, Star Mill, Nano Getter, trade name: Max Nano Getter (Ashizawa Finetech Co., Ltd.), trade name: Micro Media (Buehler Co., Ltd.), trade name: MSC Mill (Nippon Coke & Engineering Co., Ltd.), trade name: NPM (Shinmaru Enterprises Co., Ltd.), and Sand Grind (SG) Mill.
[0082] Examples of the material of the dispersion media include alumina, zirconia, silicon carbide, silicon nitride, glass, steel, stainless steel, and ceramics. The particle size of the dispersion media may be, for example, 0.3 mm or less, 0.1 mm or less, or 0.05 mm or less. This can further promote the fine particle formation of the pigment (C).
[0083] The agitator rotation speed of the dispersing machine may be, for example, 500 rpm or more and 5000 rpm or less. The mixing time may be, for example, 30 minutes or more and 200 minutes or less. The mixing temperature may be, for example, 5°C or more and 45°C or less.
[0084] [Water-based paint composition] The aqueous coating composition may contain the above-mentioned pigment dispersion and a coating film-forming resin. The aqueous coating composition may further contain a curing agent capable of reacting with the coating film-forming resin and an aqueous solvent. The aqueous solvent may be the same as the aqueous solvent exemplified as that contained in the pigment dispersion. The aqueous coating composition may be further diluted with a solvent suitable for coating.
[0085] The pigment (C) is sufficiently and stably dispersed in the aqueous coating composition. Therefore, the resulting coating film has excellent color development. The color development is obtained by comprehensively evaluating the gloss, transparency, color depth, etc. according to the type of pigment. "Having excellent color development" can also be said to mean that the color expected from the pigment is expressed in the coating film.
[0086] The pigment dispersion is blended so that the pigment (C) is, for example, 1 part by mass or more and 30 parts by mass or less per 100 parts by mass of the solid content of the coating film-forming resin contained in the aqueous coating composition. The blending amount of the pigment (C) may be 2 parts by mass or more, or may be 3 parts by mass or more. The blending amount of the pigment (C) may be 25 parts by mass or less, or may be 20 parts by mass or less.
[0087] The solid content concentration of the aqueous coating composition is, for example, 3% by mass or more and 50% by mass or less. The solid content concentration of the aqueous coating composition may be 5% by mass or more, or 7% by mass or more. The solid content concentration of the aqueous coating composition may be 45% by mass or less, or 40% by mass or less.
[0088] The solids concentration of the aqueous coating composition is measured in accordance with JIS K 5601-1-2 Heating Residue Measurement Method.
[0089] (Coating film forming resin) Examples of the film-forming resin include acrylic resin, acrylic silicone resin, polyester resin, polyurethane resin, epoxy resin, fluororesin, and silicone resin. These may be used alone or in combination of two or more. Among them, acrylic resin is preferable.
[0090] The coating film-forming resin may contain a hydroxyl-containing resin. Examples of the hydroxyl-containing resin include hydroxyl-containing acrylic resin, hydroxyl-containing polyester resin, polycarbonate polyol resin, polyether polyol resin, and polycaprolactone polyol resin. These may be used alone or in combination of two or more. Among them, the hydroxyl-containing acrylic resin may be used.
[0091] The hydroxyl value (OHV) of the hydroxyl-containing resin may be, for example, 20 mgKOH / g or more and 180 mgKOH / g or less. When the hydroxyl value of the hydroxyl-containing resin is 20 mgKOH / g or more, the breaking strength of the coating film is likely to be high. When the hydroxyl value of the hydroxyl-containing resin is 180 mgKOH / g or less, the hydrophilization of the coating film is suppressed, and the water resistance is likely to be improved. The hydroxyl value of the hydroxyl-containing resin may be 30 mgKOH / g or more, or 40 mgKOH / g or more. The hydroxyl value of the hydroxyl-containing resin may be 150 mgKOH / g or less, 140 mgKOH / g or less, 100 mgKOH / g or less, or 80 mgKOH / g or less.
[0092] The weight average molecular weight (Mw) of the hydroxyl-containing resin (A) may be, for example, 2,000 or more and 50,000 or less.
[0093] The weight average molecular weight is determined by the GPC method using polystyrene as the standard. The acid value and hydroxyl value are calculated from the monomer composition used in the preparation based on the JIS regulations.
[0094] The coating film-forming resin may be contained as an emulsion, may be contained as a dispersion, or may be contained in a state of being dissolved in a solvent. For example, an acrylic resin dispersion can be prepared by solution polymerizing the above-mentioned α,β-ethylenically unsaturated monomer and dispersing it using a basic compound. A water-soluble acrylic resin can be prepared by solution polymerizing the above-mentioned α,β-ethylenically unsaturated monomer and dissolving it in water using a basic compound.
[0095] The emulsion of the hydroxyl-containing acrylic resin can be prepared, for example, by emulsion polymerization of an α,β-ethylenically unsaturated monomer. Examples of the α,β-ethylenically unsaturated monomer include (meth)acrylic acid esters, α,β-ethylenically unsaturated monomers having an acid group, and α,β-ethylenically unsaturated monomers having a hydroxyl group. The monomers can be used alone or in combination of two or more.
[0096] Examples of (meth)acrylic acid esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, phenyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, dicyclopentadienyl (meth)acrylate, and dihydrodicyclopentadienyl (meth)acrylate. (Meth)acrylic acid esters refer to acrylic acid esters and methacrylic acid esters.
[0097] Examples of α,β-ethylenically unsaturated monomers having an acid group include acrylic acid, methacrylic acid, crotonic acid, 2-acryloyloxyethyl phthalic acid, 2-acryloyloxyethyl succinic acid, ω-carboxy-polycaprolactone mono(meth)acrylate, isocrotonic acid, α-hydro-ω-((1-oxo-2-propenyl)oxy)poly(oxy(1-oxo-1,6-hexanediyl)), maleic acid, fumaric acid, itaconic acid, 3-vinylsalicylic acid, 3-vinylacetylsalicylic acid, 2-acrylamido-2-methylpropanesulfonic acid, p-hydroxystyrene, and 2,4-dihydroxy-4′-vinylbenzophenone.
[0098] Examples of the α,β-ethylenically unsaturated monomer having a hydroxyl group include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, allyl alcohol, methallyl alcohol, and adducts of these with ε-caprolactone.
[0099] Other α,β-ethylenically unsaturated monomers may be used in combination. Examples of other α,β-ethylenically unsaturated monomers include polymerizable amide compounds, polymerizable aromatic compounds, polymerizable nitriles, polymerizable alkylene oxide compounds, polyfunctional vinyl compounds, polymerizable amine compounds, α-olefins, dienes, polymerizable carbonyl compounds, polymerizable alkoxysilyl compounds, and other polymerizable compounds.
[0100] The method of emulsion polymerization is not particularly limited. For example, an emulsifier is dissolved in an aqueous medium containing water or, if necessary, an organic solvent such as alcohol, ether (e.g., dipropylene glycol methyl ether, propylene glycol methyl ether, etc.), and an α,β-ethylenically unsaturated monomer and a polymerization initiator are dropped under heating and stirring. The α,β-ethylenically unsaturated monomer may be emulsified in advance by an emulsifier.
[0101] The polymerization initiator and emulsifier may be those commonly used by those skilled in the art. If necessary, the molecular weight may be adjusted using a chain transfer agent such as mercaptan (e.g., lauryl mercaptan) and α-methylstyrene dimer. The reaction temperature, reaction time, etc. may be appropriately selected within the range commonly used by those skilled in the art. The obtained acrylic resin emulsion is neutralized with a base as necessary.
[0102] The hydroxyl-containing acrylic resin obtained by emulsion polymerization may have a number average molecular weight of 3,000 or more. The hydroxyl-containing acrylic resin may have a hydroxyl value (solid content hydroxyl value) of 20 mgKOH / g or more and 180 mgKOH / g or less. The hydroxyl-containing acrylic resin may have an acid value (solid content acid value) of 1 mgKOH / g or more and 80 mgKOH / g or less.
[0103] (hardening agent) The aqueous coating composition may include a curing agent that reacts with the film-forming resin to form a cured coating therewith.
[0104] Examples of the curing agent include melamine resin, blocked isocyanate compound, epoxy compound, aziridine compound, carbodiimide compound, oxazoline compound, and metal ion. These may be used alone or in combination of two or more. Among them, at least one of melamine resin and blocked isocyanate compound may be used.
[0105] The melamine resin may be water-soluble or water-insoluble. The melamine resin includes a structure in which hydrogen atoms or substituents (alkyl ether groups, methylol groups, etc.) are bonded to the periphery of a melamine nucleus (triazine nucleus) via three nitrogen atoms. The melamine resin is generally composed of a polynuclear body in which a plurality of melamine nuclei are bonded to each other. The melamine resin may be a mononuclear body consisting of one melamine nucleus.
[0106] Commercially available melamine resins may be used. Examples of commercially available melamine resins include the Cymel series (trade name) manufactured by Allnex, specifically Cymel 202, Cymel 204, Cymel 211, Cymel 232, Cymel 235, Cymel 236, Cymel 238, Cymel 250, Cymel 251, Cymel 254, Cymel 266, Cymel 267, Cymel 272, Cymel 285, Cymel 301, Cymel 303, Cymel 325, Cymel 327, Cymel 350, Cymel 370, Cymel 701, Cymel 703, and Cymel 1141; and the U-Ban (trade name) series manufactured by Mitsui Chemicals. These may be used alone or in combination of two or more.
[0107] The blocked isocyanate compound can be prepared by adding a blocking agent having an active hydrogen to a polyisocyanate such as trimethylene diisocyanate, hexamethylene diisocyanate, xylylene diisocyanate, isophorone diisocyanate, or the like.
[0108] The content of the curing agent may be 10% by mass or more and 80% by mass or less of the resin solid content contained in the aqueous coating composition. The content of the curing agent may be 15% by mass or more. The content of the curing agent may be 60% by mass or less.
[0109] (others) The aqueous coating composition may contain other components such as a defoamer, an ultraviolet absorber, a light stabilizer (for example, a hindered amine), an antioxidant, a surface conditioner, a film-forming assistant, and a rust inhibitor.
[0110] [Method of manufacturing water-based paint composition] The aqueous coating composition according to the present disclosure is produced by a method comprising a step of mixing the pigment dispersion produced by the above-mentioned method with a coating film-forming resin.
[0111] The mixing conditions and mixing device may be the same as those mentioned in the method for producing the pigment dispersion.
[0112] [Painted items] The aqueous coating composition according to the present disclosure provides a coated article having a coating film with excellent color development. The coated article includes a substrate and a base coat coating film formed from the aqueous coating composition. The coated article may include a substrate, a base coat coating film formed from the aqueous coating composition, and a clear coating film disposed on the base coat coating film.
[0113] The base coat film may be one layer or two or more layers. At least one base coat film is formed from the aqueous coating composition according to the present disclosure. The components contained in each base coat film may be the same or different.
[0114] (subject to be coated) Examples of the material of the object to be coated include metal, plastic, and foam. In particular, the object may be a metal (particularly a casting), and may be a metal that can be electrocoated. Examples of such metals include iron, copper, aluminum, tin, zinc, and alloys containing these metals.
[0115] The shape of the substrate is not particularly limited, and may be flat or three-dimensional. Specific examples of the substrate include automobile bodies and parts thereof, such as passenger cars, trucks, motorcycles, and buses.
[0116] The metal substrate may be subjected to a chemical conversion treatment using a phosphoric acid-based chemical conversion treatment agent, a zirconium-based chemical conversion treatment agent, or the like, and may be subjected to an electrodeposition coating. The electrodeposition coating composition may be of the cationic type or the anionic type. The cationic electrodeposition coating composition can form a coating film having excellent corrosion resistance.
[0117] The metal substrate may have an electrodeposition coating and an intermediate coating thereon. The intermediate coating is usually provided for the purpose of improving the adhesion and durability of the multi-layer coating. The intermediate coating composition may contain, for example, a film-forming resin, a curing agent, a color pigment, and an extender pigment. The film-forming resin and the curing agent may be the same as those contained in the aqueous coating composition according to the present disclosure.
[0118] (Base coat film) At least one base coat film is formed from the above-mentioned aqueous coating composition. The thickness of the base coat film may be 0.2 μm or more and 50 μm or less. The thickness of the base film may be 3 μm or more. The thickness of the base film may be 40 μm or less, 30 μm or less, or 20 μm or less.
[0119] (Clear coating) The clear coating film protects the base coating film. The thickness of the clear coating film may be, for example, 10 μm or more and 80 μm or less. The thickness of the clear coating film may be 20 μm or more. The thickness of the clear coating film may be 60 μm or less.
[0120] The clear coating film is formed by a clear coating composition. The clear coating composition may be solvent-based, water-based, or powder-type. From the viewpoint of transparency or acid etching resistance, the solvent-based clear coating composition may contain an acrylic resin and / or a polyester resin as a coating film-forming resin, and an amino resin and / or an isocyanate as a curing agent. The solvent-based clear coating composition may also contain an acrylic resin and / or a polyester resin having a carboxylic acid and / or an epoxy group.
[0121] The clear coating composition may contain the above-mentioned various pigments within a range that does not impair the transparency and the effect of the coating composition according to the present disclosure. The clear coating composition may contain various additives as necessary. Examples of additives include ultraviolet absorbers, antioxidants, defoamers, surface conditioners, and pinhole inhibitors.
[0122] [Manufacturing method of coated articles] The method for producing a coated article will be described using as an example a coated article having a substrate, a base coat film, and a clear coat film.
[0123] A coated article having a base coat film and a clear coat film can be obtained, for example, by sequentially coating an aqueous coating composition according to the present disclosure and a clear coating composition on a substrate, and then curing both of them simultaneously. After coating the aqueous coating composition, preheating may be performed before coating the clear coating composition.
[0124] Examples of the coating method include air spray coating, airless spray coating, electrostatic spray coating, multi-stage coating (preferably two-stage coating) using air electrostatic spray coating, and coating that combines air electrostatic spray coating with a rotary atomizer-type electrostatic coater.
[0125] Curing of each coating composition is carried out, for example, under conditions of a heating temperature of 80° C. to 180° C. (preferably 100° C. to 160° C.) and a heating time of 5 minutes to 60 minutes (preferably 10 minutes to 30 minutes). EXAMPLES
[0126] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited thereto. In the examples, "parts" and "%" are by weight unless otherwise specified.
[0127] [Production Example 1-1] Production of copolymer (A-1) A reaction vessel equipped with a stirrer, a temperature controller, a cooling tube, and a dropping device was charged with 78 parts of dipropylene glycol monomethyl ether, and the temperature was raised to 120° C. with stirring to reflux. Next, a solution of 15 parts of 2-(dimethylamino)ethyl methacrylate, 60 parts of a monomer having a polyoxyalkylene structure (product name: PME-1000, manufactured by NOF Corp., methoxypolyethylene glycol-methacrylate), 19 parts of 2-hydroxyethyl methacrylate, and 6 parts of butyl acrylate, 0.5 parts of Kayaester O (manufactured by NOF Corp.), and 76 parts of dipropylene glycol monomethyl ether was dropped over 3 hours and reacted. As a post-shot, a polymerization initiator solution in which 0.3 parts of Kayaester O (manufactured by NOF Corp.) was dissolved in 11 parts of dipropylene glycol monomethyl ether was further dropped over 0.5 hours as a polymerization initiator, and the mixture was polymerized by stirring for 0.5 hours to obtain a copolymer (A-1). Next, the solvent was distilled off by vacuum distillation at 90°C, and then 100 parts of ion-exchanged water was added to 1000 parts of the copolymer (A-1) and stirred to obtain an aqueous solution of the copolymer (A-1) (solid content 50% by mass). The resulting copolymer (A-1) had a hydroxyl value of 82 mgKOH / g and a weight average molecular weight of 30,000.
[0128] [Production Examples 1-2 to 1-14] Production of Copolymers (A-2) to (A-12), (a-1) and (a-2) Copolymers (A-2) to (A-12), (a-1) and (a-2) were prepared in the same manner as in Production Example 1-1, except that the monomers shown in the table below were used in the amounts shown in Table 1.
[0129] [Table 1]
[0130] [Production Example 2] Production of acrylic resin emulsion 633 parts of deionized water was added to the reaction vessel, and the temperature was raised to 80°C while mixing and stirring in a nitrogen stream. Separately, 75.65 parts by mass of styrene (ST), 178.96 parts by mass of methyl methacrylate (MMA), 75.94 parts by mass of n-butyl acrylate (BA), 64.45 parts by mass of 2-ethylhexyl acrylate (2-EHA), and 105 parts by mass of hydroxyethyl methacrylate (HEMA) were mixed to prepare a monomer mixture for the first stage. Next, this monomer mixture was mixed with 25 parts of Aqualon HS-10 (polyoxyethylene alkylpropenyl phenyl ether sulfate, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), 25.0 parts of Adeka Reasoap NE-20 (α-[1-[(allyloxy)methyl]-2-(nonylphenoxy)ethyl]-ω-hydroxyoxyethylene, manufactured by Asahi Denka Co., Ltd.), and 400 parts of deionized water to prepare a monomer emulsion. Separately, an initiator solution consisting of 1.2 parts of ammonium persulfate and 500 parts of deionized water was prepared. The monomer emulsion and the initiator solution were dropped into the reaction vessel in parallel over 1.5 hours. After the dropwise addition was completed, the mixture was aged at the same temperature for 1 hour.
[0131] Further, 53.65 parts by mass of styrene (ST), 178.96 parts by mass of methyl methacrylate (MMA), 75.94 parts by mass of n-butyl acrylate (BA), 64.45 parts by mass of 2-ethylhexyl acrylate (2-EHA), 105 parts by mass of hydroxyethyl methacrylate (HEMA), and 22 parts by mass of acrylic acid were mixed to prepare a second-stage monomer mixture. Next, this monomer mixture was mixed with 10 parts of Aqualon HS-10 and 250 parts of deionized water to prepare a monomer emulsion. Separately, an initiator solution consisting of 3.0 parts of ammonium persulfate and 500 parts of deionized water was prepared. The monomer emulsion and the initiator solution were dropped in parallel into the above reaction vessel over 1.5 hours. After the dropwise addition was completed, the mixture was aged at the same temperature for 2 hours.
[0132] The reaction product was then cooled to 40°C and filtered through a 400 mesh filter. Finally, 100 parts of deionized water and 1.6 parts of dimethylaminoethanol were added to the reaction product to adjust the pH to 6.5. In this way, an acrylic resin emulsion was obtained with an average particle size of 150 nm, a solid content of 35 mass%, a solid content acid value of 20 mgKOH / g, and a hydroxyl value of 100 mgKOH / g.
[0133] [Production Example 3] Production of water-soluble acrylic resin 23.89 parts of tripropylene glycol methyl ether and 16.11 parts of propylene glycol methyl ether were added to the reaction vessel, and the mixture was heated to 105°C while being mixed and stirred in a nitrogen stream. Next, a monomer mixture containing 13.1 parts of methyl methacrylate, 68.4 parts of ethyl acrylate, 11.6 parts of 2-hydroxyethyl methacrylate, and 6.9 parts of methacrylic acid was prepared, and an initiator solution consisting of 100 parts of the monomer mixture, 10.0 parts of tripropylene glycol methyl ether, and 1 part of tertiary butyl peroxy 2-ethylhexanoate was dropped into the reaction vessel in parallel over a period of 3 hours. After the dropwise addition, the mixture was aged at the same temperature for 0.5 hours.
[0134] Further, an initiator solution consisting of 5.0 parts of tripropylene glycol methyl ether and 0.3 parts of tertiary butyl peroxy 2-ethylhexanoate was added dropwise to the reaction vessel over 0.5 hours. After the completion of the addition, the mixture was aged at the same temperature for 2 hours.
[0135] After 16.1 parts of the solvent was distilled off at 110°C under reduced pressure (70 torr) using a solvent remover, 204 parts of deionized water and 7.1 parts of dimethylaminoethanol were added to obtain a water-soluble acrylic resin solution. The solid content of the obtained water-soluble acrylic resin solution was 30% by mass, the solid content acid value was 40 mgKOH / g, the hydroxyl value was 50 mgKOH / g, and the viscosity was 140 poise (E-type viscometer 1 rpm / 25°C).
[0136] The weight average molecular weight was measured using a GPC apparatus "HLC8220GPC" (trade name, manufactured by Tosoh Corporation) and four columns "Shodex KF-606M" and "Shodex KF-603" (both trade names, manufactured by Showa Denko K.K.), under the following conditions: mobile phase: tetrahydrofuran, measurement temperature: 40°C, flow rate: 0.6 cc / min, and detector: RI.
[0137] The acid value and hydroxyl value were calculated from the monomer composition used in the preparation, based on the JIS standard.
[0138] Details of the organic acids (B) used in the examples and comparative examples are shown in Table 2.
[0139] [Table 2]
[0140] [Example 1] Preparation of pigment dispersion (blue) A first mixture was obtained by adding 8.3 parts (solid content mass) of copolymer (A-1) and 60 parts of ion-exchanged water to a stirrer. 2.2 parts of organic acid (B-1) were added to the first mixture and stirred, and 0.5 parts of defoamer (BYK-011, manufactured by ALTNA) were further added and stirred to obtain a second mixture. 15 parts of phthalocyanine blue (blue pigment, manufactured by Toyo Color Co., Ltd., product name: LIONOL BLUE 7186-PM) were added to the second mixture and stirred, and ion-exchanged water was added to make the total 100 parts. The resulting mixture was dispersed in a batch-type SG mill filled with 0.5 mm zirconia beads as a dispersion medium at a volumetric filling rate of 70%, to obtain a pigment dispersion (blue).
[0141] [Examples 2 to 19, Comparative Examples 1 to 8] Preparation of pigment dispersion (blue) A pigment dispersion (blue) was prepared in the same manner as in Example 1, except that the type or amount of copolymer (A) and the type or amount of organic acid (B) were changed as shown in Table 3.
[0142] Preparation of [Example 20] 2.8 parts (solid content mass) of copolymer (A-1) and 19 parts of ion-exchanged water were added to the stirrer and stirred to obtain a first mixture. 0.8 parts of organic acid (B-1) were added to the first mixture and stirred, and then 0.5 parts of defoamer (BYK-011, manufactured by ALTNA) were added and stirred to obtain a second mixture. 73.0 parts of titanium oxide (white pigment, manufactured by Ishihara Sangyo Kaisha, Ltd. CR-97) were added to the second mixture and stirred, and ion-exchanged water was added so that the total amount became 100 parts. The obtained mixture was dispersed in a paint conditioner filled with 0.6 mm zircon beads as a dispersion medium at a volume filling rate of 70%, to obtain a pigment dispersion (white).
[0143] [Example 21 and Comparative Examples 9 and 10] Preparation of Pigment Dispersion (White) A pigment dispersion (white) was obtained by the same procedure as in Example 20, except that the type or amount of copolymer (A) and the type or amount of organic acid (B) were changed as shown in Table 4.
[0144] [Example 22] Preparation of pigment dispersion (black) 12.5 parts (solid content mass) of copolymer (A-1) and 50.0 parts of ion-exchanged water were added to the stirrer and stirred to obtain a first mixture. 3.2 parts of organic acid (B-1) were added to the first mixture and stirred, and then 0.5 parts of defoamer (BYK-011, manufactured by ALTNA) were added and stirred to obtain a second mixture. 17.5 parts of carbon black (black pigment, Raben 5000 manufactured by BILRA CARBON) were added to the second mixture and stirred, and ion-exchanged water was added so that the total amount became 100 parts. The obtained mixture was dispersed in a batch type SG mill filled with 0.5 mm zircon beads as a dispersion medium at a volume filling rate of 70%, to obtain a pigment dispersion (black).
[0145] [Example 23 and Comparative Examples 11 and 12] Preparation of Pigment Dispersion (Black) A pigment dispersion (black) was obtained by the same procedure as in Example 22, except that the type or amount of copolymer (A) and the type or amount of organic acid (B) were changed as shown in Table 5.
[0146] [Example 24] Preparation of pigment dispersion (red) 7.8 parts (solid content mass) of copolymer (A-1) and 45.0 parts of ion-exchanged water were added to the stirrer and stirred to obtain a first mixture. 2.0 parts of organic acid (B-1) were added to the first mixture and stirred, and then 0.5 parts of defoamer (BYK-011, manufactured by ALTNA) were added and stirred to obtain a second mixture. 34.5 parts of diketopyrrolopyrrole (red pigment, Irgazin Rubine L 4025 manufactured by BASF) were added to the second mixture and stirred, and ion-exchanged water was added so that the total amount became 100 parts. The resulting mixture and the resulting pigment dispersion were dispersed in a batch type SG mill filled with 0.6 mm zircon beads as a dispersion medium at a volume filling rate of 70%, to obtain a pigment dispersion (red).
[0147] [Comparative Example 13] Preparation of pigment dispersion (red) A pigment dispersion (red) was obtained by the same procedure as in Example 24, except that the type or amount of copolymer (A) and the type or amount of organic acid (B) were changed as shown in Table 6.
[0148] [evaluation] The pigment dispersions of the Examples and Comparative Examples were evaluated as follows. (1) Average particle diameter The pigment dispersion was infinitely diluted with ion-exchanged water, and the 50% volume particle size (D50) of the pigment in the pigment dispersion was measured using a particle size distribution analyzer (product name: UPA-150, manufactured by Microtrac) by dynamic light scattering. The smaller the particle size, the higher the pigment dispersibility.
[0149] (2) Viscosity The viscosity was measured at 25° C. and a rotation speed of 5 rpm using a viscosity measuring device (product name: VISCOMETER TV-25, manufactured by Toki Sangyo Co., Ltd.).
[0150] (3) Color development of the coating (3-1) Pigment dispersion containing blue pigment, red pigment, and black pigment A clear base was prepared by mixing 210 parts of the water-soluble acrylic resin (solid content 30%) of Production Example 3 and 30 parts of Cymel 327 (mixed alkylated melamine resin, manufactured by Allnex, solid content 90%). A pigment dispersion was mixed into the clear base so that the mass of the pigment was 10 parts per 90 mass parts of the solid content of the clear base, to obtain an aqueous coating composition for evaluation.
[0151] The obtained aqueous coating composition for evaluation was applied to a glass plate of 15 cm x 10 cm and heat cured at 140°C for 20 minutes to obtain a coating film for evaluation. The appearance of the obtained coating film for evaluation was visually observed, and the color development was evaluated according to the following criteria. The evaluation results are shown in Tables 3 to 5, 7, and 8. A rating of more than B can be said to be excellent in color development.
[0152] Evaluation criteria for coatings formed with pigment dispersion (blue) A: Transparent and has a strong blue tint A-: Transparent, but slightly less blue B: Slightly cloudy and slightly less blue. C: Cloudy and weak blue color
[0153] Evaluation criteria for coatings formed with pigment dispersion (black) A: Shiny and jet black B: Between criteria A and C C: White blur
[0154] Evaluation criteria for coatings formed with pigment dispersion (red) A: Transparent and deep red B: Slightly cloudy and slightly less red C: Cloudy
[0155] (3-2) Pigment dispersion containing white pigment The pigment dispersion was applied to a 15 cm x 10 cm glass plate and heated at 140°C for 20 minutes to obtain a coating film for evaluation. The obtained coating film for evaluation was left to stand at 23°C, and then the 60° gloss value was measured using a Macrogloss glossmeter (manufactured by BYK Gardner). The 60° gloss value was evaluated according to the following criteria. The evaluation results are shown in Table 6. The higher the 60° gloss value, the higher the white color development. A rating of more than B can be said to be excellent in color development.
[0156] Evaluation criteria for coatings formed using pigment dispersion (white) A: 60° gloss value is 80 or more B: 60° gloss value is 60 or more and less than 80 C: 60° gloss value is less than 60
[0157] [Table 3]
[0158] [Table 4]
[0159] [Table 5]
[0160] [Table 6]
[0161] [Table 7]
[0162] [Table 8]
[0163] In the pigment dispersions of Examples 1 to 24, the average particle size of the pigment was small and the viscosity was kept low.
[0164] In Comparative Examples 1 and 2, the average particle size of the pigment (C) was large. The pigment dispersions of Comparative Examples 1 and 2 did not contain organic acid (B), so it is believed that the hydrophobic pigment phthalocyanine blue was not sufficiently dispersed. In Comparative Example 3, when oleylamine was used instead of organic acid (B), the average particle size of the pigment (C) was large. It is believed that the oleylamine used in Comparative Example 3 could not function as a counter ion of the copolymer (A), the charge balance was lost, and the aggregation of the pigments (C) was not suppressed. In Comparative Example 4, when polyoxyethylene oleyl ether was used instead of organic acid (B), the average particle size of the pigment (C) could not be sufficiently reduced, and the viscosity of the pigment dispersion increased. It is believed that the polyoxyethylene oleyl ether used in Comparative Example 4 could not function sufficiently as a counter ion of the copolymer (A), so the aggregation of the pigments (C) was not sufficiently suppressed, and further, a specific interaction occurred between polyoxyethylene oleyl ether and phthalocyanine blue, resulting in an extremely high viscosity. In Comparative Examples 5 and 6, the average particle size of the pigment (C) was large, and the viscosity of the pigment dispersion was also high. It is believed that the organic acid used in Comparative Examples 5 and 6 had a short hydrocarbon group, and therefore aggregation between the pigments was not sufficiently suppressed. In Comparative Example 7, the average particle size of the pigment (C) was large. It is believed that this is because the copolymer (A) used in Comparative Example 7 did not have a nitrogen-containing group, and therefore could not function as a counter ion for the organic acid (B), and therefore aggregation between the pigments (C) was not suppressed.
[0165] The coating films formed from the aqueous coating compositions produced using the pigment dispersions of Comparative Examples 1 to 7 all had particularly low transparency.
[0166] The pigment could not be dispersed in Comparative Example 8. This is believed to be because the copolymer used in Comparative Example 8 did not have a polyoxyalkylene chain, and therefore had low affinity with the aqueous solvent, and the copolymer itself could not be dispersed in the aqueous solvent, and as a result, the pigment (C) could not be dispersed.
[0167] In Comparative Examples 9 to 13, no organic acid (B) was used. In Comparative Example 9, the average particle size of the pigment (C) was large, and in particular, an increase in viscosity was confirmed. In Comparative Example 9, since the organic acid (B) was not used, it is considered that titanium oxide, which is generally basic, had difficulty in adsorbing the resin component, and therefore was difficult to disperse. Furthermore, titanium oxide has a large specific gravity and is prone to settling, and in addition, it was insufficiently dispersed, which is considered to have led to an excessive increase in viscosity. In Comparative Example 10, it was also difficult to disperse titanium oxide, and an evaluation test could not be performed.
[0168] In Comparative Examples 11 and 12, since carbon black, an acidic pigment, was used, it was possible to disperse it using the copolymer (A), but the average particle size of the pigment (C) was relatively large and the dispersibility was insufficient. In Comparative Example 12, an increase in viscosity was also confirmed.
[0169] In Comparative Example 13, the pigment had a relatively small average particle size, but the color development was poor. This is thought to be because the pigment was in an unstable dispersed state in the pigment dispersion liquid, and the pigment partially aggregated during the production of the aqueous coating composition.
[0170] [Example 25] Preparation of water-based paint composition and coated article (1) Production of water-based paint composition An aqueous coating composition with a solids concentration of 20% was prepared by mixing 160 parts of the acrylic resin emulsion of Production Example 2, 1 part of dimethylaminoethanol, 33 parts of the water-soluble acrylic resin of Production Example 3 (solids content 30% by mass), 38 parts of a melamine resin (Cymel 204, manufactured by Mitsui Cytec Co., Ltd., mixed alkylated melamine resin, solids content 80%), 10 parts of a bifunctional polyether polyol (Primepol PX-1000, manufactured by Sanyo Chemical Industries, Ltd.), and 30 parts of the pigment dispersion of Example 1 (solids content 26%) and diluting with deionized water.
[0171] (2) Manufacture of painted products A cationic electrodeposition coating composition "Power Top U-50)" (manufactured by Nippon Paint Automotive Coatings) was electrocoated on a zinc phosphate-treated dull steel plate measuring 0.8 mm in thickness, 30 cm in length, and 40 cm in width, so that the dry film thickness was 20 μm, and the plate was baked at 160°C for 30 minutes. An intermediate coating composition "OP-30P Middle Gray" (manufactured by Nippon Paint Automotive Coatings, polyester-melamine paint, pre-diluted for 25 seconds (measured at 20°C using a No. 4 Ford cup)) was air-sprayed on the resulting plate using an Anest Iwata air spray gun W-101-132G so that the dry film thickness was 35 μm, and the plate was baked and cured at 140°C for 30 minutes. In this way, a coated object having an electrodeposition coating film and an intermediate coating film was obtained.
[0172] An aqueous base paint composition (Nippon Paint Automotive Coatings, aqueous base AR-3020-1 (gray metallic)) was air spray painted onto the substrate at a room temperature of 23°C and a humidity of 68% to a dry film thickness of 12μm. After setting for 4 minutes, the coating was preheated at 80°C for 5 minutes. Next, the aqueous paint composition prepared above was air spray painted onto the substrate at a room temperature of 23°C and a humidity of 68% to a dry film thickness of 12μm. After setting for 4 minutes, the coating was preheated at 80°C for 5 minutes.
[0173] Next, a clear paint (PolyureExcel O-1200 (product name), a two-liquid acrylic urethane organic solvent-based clear paint containing a polyisocyanate compound, manufactured by Nippon Paint Automotive Coatings Co., Ltd.) was applied using a rotary atomizing electrostatic coater so that the dry film thickness was 35 μm. Finally, the product was heated at 80°C for 20 minutes to obtain a coated article having a multi-layer coating film. The resulting coating film was transparent and had a strong bluish tint.
[0174] The present disclosure includes the following aspects. [1] A composition comprising a copolymer (A), a hydrocarbon group-containing acidic compound (B), a pigment (C), and an aqueous solvent (D), The copolymer (A) is The copolymer has a first segment (a1) derived from a nitrogen-containing polymerizable unsaturated monomer having at least one of a tertiary amino group and a nitrogen-containing heterocyclic group, and a second segment (a2) derived from a polymerizable unsaturated monomer having a polyoxyalkylene chain, The hydrocarbon group-containing acidic compound (B) is A pigment dispersion having (b1) a saturated or unsaturated hydrocarbon group having 5 to 23 carbon atoms, and (b2) at least one acid group selected from the group consisting of a carboxy group, a phosphoric acid group, a sulfonic acid group, and a phenol group. [2] The pigment dispersion according to the above-mentioned [1], wherein the ratio of the equivalent of the acid group contained in the hydrocarbon group-containing acidic compound (B) to the total equivalent of the tertiary amino group and the nitrogen-containing heterocyclic group contained in the copolymer (A) (acid group / tertiary amino group and nitrogen-containing heterocyclic group) is 0.5 or more and 2 or less. [3] The copolymer (A) further has a third segment (a3) derived from a polymerizable unsaturated monomer other than the nitrogen-containing polymerizable unsaturated monomer and the polymerizable unsaturated monomer having a polyoxyalkylene chain, In the copolymer (A), The mass proportion of the first segment (a1) is 5 mass% or more and 30 mass% or less, The mass proportion of the second segment (a2) is 20 mass% or more and 80 mass% or less, The pigment dispersion according to the above [1] or [2], wherein the mass proportion of the third segment (a3) is 10 mass % or more and 60 mass % or less. [4] the third segment (a3) contains a segment (a31) derived from a hydroxyl group-containing polymerizable saturated monomer, The pigment dispersion liquid according to [3] above, wherein the mass proportion of the segment (a31) in the copolymer (A) is 10 mass % or more and 30 mass % or less. [5] Any one of the pigment dispersions [1] to [4] above, and a film-forming resin. [6] A step of adding and mixing a hydrocarbon group-containing acidic compound (B) to a first mixture containing an aqueous solvent (D) and a copolymer (A) to obtain a second mixture; and adding and mixing a pigment (C) to the second mixture, The copolymer (A) is a first segment (a1) derived from a nitrogen-containing polymerizable unsaturated monomer having at least one of a tertiary amino group and a nitrogen-containing heterocyclic group, and a second segment (a2) derived from a polymerizable unsaturated monomer having a polyoxyalkylene chain; The hydrocarbon group-containing acidic compound (B) is A method for producing a pigment dispersion having a saturated or unsaturated hydrocarbon group (b1) having 5 to 23 carbon atoms and at least one acid group (b2) selected from the group consisting of a carboxy group, a phosphoric acid group, a sulfonic acid group, and a phenol group. [7] A method for producing an aqueous coating composition, comprising the step of mixing the pigment dispersion produced by the method described in [6] above with a coating film-forming resin. [Industrial Applicability]
[0175] The pigment dispersion of the present invention can disperse pigments sufficiently and stably regardless of the type of pigment and without causing an increase in viscosity, and therefore can be used in various aqueous coating compositions.
Claims
1. A composition comprising a copolymer (A), a hydrocarbon group-containing acidic compound (B), a pigment (C), and an aqueous solvent (D), The copolymer (A) is a first segment (a1) derived from a nitrogen-containing polymerizable unsaturated monomer having at least one of a tertiary amino group and a nitrogen-containing heterocyclic group, and a second segment (a2) derived from a polymerizable unsaturated monomer having a polyoxyalkylene chain; The hydrocarbon group-containing acidic compound (B) is A pigment dispersion having (b1) a saturated or unsaturated hydrocarbon group having 5 to 23 carbon atoms, and (b2) at least one acid group selected from the group consisting of a carboxy group, a phosphoric acid group, a sulfonic acid group, and a phenol group.
2. 2. The pigment dispersion according to claim 1, wherein a ratio of an equivalent of an acid group contained in the hydrocarbon group-containing acidic compound (B) to a total equivalent of a tertiary amino group and a nitrogen-containing heterocyclic group contained in the copolymer (A) (acid group / tertiary amino group and nitrogen-containing heterocyclic group) is 0.5 or more and 2 or less.
3. The copolymer (A) further has a third segment (a3) derived from a polymerizable unsaturated monomer other than the nitrogen-containing polymerizable unsaturated monomer and the polymerizable unsaturated monomer having a polyoxyalkylene chain, In the copolymer (A), The mass proportion of the first segment (a1) is 5 mass% or more and 30 mass% or less, The mass ratio of the second segment (a2) is 20 mass% or more and 80 mass% or less, The pigment dispersion according to claim 1 or 2, wherein a mass ratio of the third segment (a3) is 10 mass % or more and 60 mass % or less.
4. The third segment (a3) includes a segment (a31) derived from a hydroxyl group-containing polymerizable saturated monomer, The pigment dispersion liquid according to claim 3 , wherein a mass ratio of the segment (a31) in the copolymer (A) is 10 mass % or more and 30 mass % or less.
5. The pigment dispersion according to claim 1 or 2, and a film-forming resin.
6. A step of adding and mixing a hydrocarbon group-containing acidic compound (B) to a first mixture containing an aqueous solvent (D) and a copolymer (A) to obtain a second mixture; and adding and mixing a pigment (C) to the second mixture, The copolymer (A) is a first segment (a1) derived from a nitrogen-containing polymerizable unsaturated monomer having at least one of a tertiary amino group and a nitrogen-containing heterocyclic group, and a second segment (a2) derived from a polymerizable unsaturated monomer having a polyoxyalkylene chain; The hydrocarbon group-containing acidic compound (B) is A method for producing a pigment dispersion liquid, comprising: a saturated or unsaturated hydrocarbon group (b1) having 5 to 23 carbon atoms; and at least one acid group (b2) selected from the group consisting of a carboxy group, a phosphoric acid group, a sulfonic acid group, and a phenol group.
7. A method for producing an aqueous coating composition, comprising the step of mixing the pigment dispersion produced by the method according to claim 6 with a film-forming resin.
Citation Information
Patent Citations
Resin for dispersing pigment
JP2003012744A
Electrodeposition coating composition
JP2009227820A
Pigment dispersing resin
JP2013221131A
Water paint composition
JP2014005399A
Coating composition
JP2015028096A